Hudba a interpretace : k otázkám analýzy hudebního výkonu - Lubomír Spurný; Petr Fančal (Musicologica Brunensia, 2017)
This study presents a current approach to music performance analysis. The analysis of sound recordings is still a relatively new discipline of musicology although the approximate 120 years history of the musical data recording offers a wide range of possibilities. Musical recordings are preferable to live production in terms of the description of time resources in music for they allow more detailed and repeated measurement of time periods. The effort of musicology research is to find objective parameters and data from typically sound and time complicated musical recording or production in real time, which can be clearly and distinctly documented, analyzed and compared. The acquisition of this data in musicology research has always been the domain of a music theorist in the role of a listener of a live production or a recording, registering noticeable quantitative parameters of the music stream. Current attempts to use algorithmic tools in this field focus typically on tempo and dynamics. Nowadays, the practice of recording analysis is aided occasionally by various software tools for determining specific categories, such as beat extraction and spectral analysis. We are inspired by some foreign works. In the plethora of current production we were intrigued mostly by the work by José Antonio Bowen, Nicholas Cook and the activity of authors concentrated around the Center for History and Analysis of Recorded Music (CHARM). While this topic is often discussed in the anglo-american musicology on a local scale this topic is rather marginal. A rare exception is the work of Milan Kuna and Miloš Bláha Time and Music. About the dramaturgy of the resources in the musical and interpretative performances (1982).